Elucidation of Akkermansia muciniphila Probiotic Traits Driven by Mucin Depletion - Shin, Jongoh; Noh, Jung-Ran; Chang, Dong-Ho; Kim, Yong-Hoon; Kim, Myung Hee; Lee, Eaum Seok; Cho, Suhyung; Ku, Bon Jeong; Rhee, Moon-Soo; Kim, Byoung-Chan; Lee, Chul-Ho; Cho, Byung-Kwan (Frontiers in Microbiology, 2019)
Akkermansia muciniphila is widely considered a next-generation beneficial microbe. This bacterium resides in the mucus layer of its host and regulates intestinal homeostasis and intestinal barrier integrity by affecting host signaling pathways. However, it remains unknown how the expression of genes encoding extracellular proteins is regulated in response to dynamic mucosal environments. In this study, we elucidated the effect of mucin on the gene expression and probiotic traits of A. muciniphila. Transcriptome analysis showed that the genes encoding most mucin-degrading enzymes were significantly upregulated in the presence of mucin. By contrast, most genes involved in glycolysis and energy metabolic pathways were upregulated under mucin-depleted conditions. Interestingly, the absence of mucin resulted in the upregulation of 79 genes encoding secreted protein candidates, including Amuc-1100 as well as members of major protein secretion systems. These transcript level changes were consistent with the fact that administration of A. muciniphila grown under mucin-depleted conditions to high-fat diet-induced diabetic mice reduced obesity and improved intestinal barrier integrity more efficiently than administration of A. muciniphila grown under mucin-containing conditions. In conclusion, mucin content in the growth medium plays a critical role in the improvement by A. muciniphila of high-fat diet-induced obesity, intestinal inflammation, and compromised intestinal barrier integrity related to a decrease in goblet cell density. Our findings suggest the depletion of animal-derived mucin in growth medium as a novel principle for the development of A. muciniphila for human therapeutics.